Influence of Fluorine in Atmospheric Waste on Mulberry Trees in Surkhandarya Regions of the Southern Region of our Republic - Samatova Sayyora Usmanovna; Daniyarov Umirzak Tukhtamuradovich (Genius Publishing Group, 2023)
The change in the intensity of respiration of mulberry trees depending on the season depends primarily on temperature and humidity, as well as the time of exposure to aluminum emissions from plants. The intensity of respiration of mulberry leaves decreases by 15% in April, by 20% in May, by 39% in June, and by almost 50% by October
Keywords: leaf; aluminum plant; fluorine; chemical